Sharia Stocks in Times of Crisis: A Study on the Influence of Macroeconomic Factors during the Covid-19 Pandemic - Tripuspitorini, Fifi Afiyanti; Setiawan, Setiawan; Dewi, Rani Putri Kusuma (Indonesian Journal of Economics and Management, 2023)
Indonesia offers various sharia-compliant stock options, with the Indonesian Sharia Stock Index (ISSI) being one such alternative. While ISSI instills confidence in investors by aligning with sharia principles, it does not automatically shield itself from macroeconomic challenges. Therefore, it remains crucial to consider macroeconomic factors when investing in Islamic stocks, especially amid the uncertainties of the Covid-19 pandemic. This study aims to explore the impact of macroeconomic factors on Islamic stock prices during the pandemic, employing a quantitative approach with secondary data. The variables encompass ISSI price (dependent), along with inflation, interest rates, and exchange rates (independent). The research involves descriptive statistics and Structural Equation Modeling (SEM) for inferential analysis, facilitated by the WarpPLS application. The findings reveal that, amid the Covid-19 pandemic, only the interest rates variable significantly and negatively influences ISSI.